The Academy of Management Member—Revisited - Forsgren, Roderick A. (Academy of Management Journal, 1974)
The article looks at a follow-up to a report which compares the changes in the profile of the Academy of Management members of 1967 with the members of 1972. The author notes that not only has the average age lowered from 46 to 43, but the Academy is also comprised of a larger percentage of members who have not yet completed their doctorates. More than one half of all respondents had not received a promotion, with 80 percent reported receiving only one in their professional career. There is also a minor shift toward the increased size of respondents' institutions.